The Role of the Private Sector in PreSchool Education - Allamurodova Ruxsora Abdinazarovna; Rahimova Guzalxon Olimjonovna; Karimova Mashhura Rustamjon qizi (Genius Journals, 2023)
In the Address of the President to the Oliy Majlis and our people, the most important tasks of the further development of our country, the priorities of the domestic and foreign policy were described, special attention was paid to the issue of providing decent education to young people, especially children of preschool age, and covering them with this education.
Keywords: preschool education; From the moment a child is born; increases